Increasing learning interest in accounting students through the game simulation accounting cycle - Suryani, Pesi; Daurrohmah, Wirajuang; Tantri, Sakina Nusarifa (Enrichment : Journal of Management, 2023)
There is a shift in the characteristics of Universitas Terbuka students from students who are already working or of mature age to the millennial generation and Generation Z. Inevitably, this encourages study programs to innovate according to the times, including the use of game simulations to increase student interest in learning, especially accounting study program students who come from Generation Z. The purpose of this study is to analyze the increase in student learning interest through game simulation. The object of this research is students of accounting study programs with semester 2-7 criteria. To find out the results of students' interests and responses using observation methods, pre-test and post-test assessments, and questionnaires. This study shows that using the game simulation accounting cycle increases student interest in learning and understanding the basics of accounting. The implication of this research is that the study program is able to innovate through innovative products to increase students' learning interest.